Progress in Flight Dynamics, Guidance, Navigation, Control, Fault Detection, and Avionics 2013
DOI: 10.1051/eucass/201306423
|View full text |Cite
|
Sign up to set email alerts
|

A model-based solution for fault diagnosis of thruster faults: application to the rendezvous phase of the mars sample return mission

Abstract: This paper addresses the design of model-based fault diagnosis schemes to detect and isolate faults occurring in the orbiter thrusters of the Mars Sample Return (MSR) mission. The proposed fault diagnosis method is based on a H(0) ¦lter with robust poles assignment to detect quickly any kind of thruster faults and a cross-correlation test to isolate them. Simulation results from the MSR ¤high-¦delity¥ nonlinear simulator provided by Thales Alenia Space demonstrate that the proposed method is able to diagnose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The first step in building a prognostics system, as published in the ISO standard, is the identification of the set of failure modes (FM), their influence factors on each other and the detection measures (descriptors) that allow to track the evolution of the degradation. The international standard IEC 60812 [10] has presented a procedure named "Procedure for failure mode and effects analysis (FMECA)", which helps the identification of all the failure modes for a specific system, by the analysis of its subsystem s and components. Also, the FMECA method classifies the FMs using risk priority numbers (RPN) that are calculated with three failure mode parameters: occurrence (Occ), detection (Det) and severity (Sev).…”
Section: Prognostics Processmentioning
confidence: 99%
“…The first step in building a prognostics system, as published in the ISO standard, is the identification of the set of failure modes (FM), their influence factors on each other and the detection measures (descriptors) that allow to track the evolution of the degradation. The international standard IEC 60812 [10] has presented a procedure named "Procedure for failure mode and effects analysis (FMECA)", which helps the identification of all the failure modes for a specific system, by the analysis of its subsystem s and components. Also, the FMECA method classifies the FMs using risk priority numbers (RPN) that are calculated with three failure mode parameters: occurrence (Occ), detection (Det) and severity (Sev).…”
Section: Prognostics Processmentioning
confidence: 99%
“…The active FTC approach is to respond to the failure by reconfiguring the remaining (often redundant) system elements based on real-time information from a fault detection and diagnosis (FDD) scheme. Numerous active FTC strategies have been studied for spacecraft missions in the past decades, for instance, the work of Chen et al [30] and Patton et al [31] about the Mars Express mission, the work reported in Fonood et al [32][33] and Henry et al [34] about the Mars Sample Return (MSR) mission, and the work of Henry [35] about the Microscope satellite. In contrast to active FTC approach, neither an FDD scheme nor a controller reconfiguration mechanism is needed in the passive approach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, autonomous spacecrafts have become a key technology for increasing their survival capability. Various researchers have developed diagnosis systems to detect and isolate faults that can appear in a spacecraft [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous fault diagnosis systems have been developed to detect and isolate the thrusters' failures. Most of these systems have been based on an analytic method using a mathematical model [6,14].…”
Section: Introductionmentioning
confidence: 99%